What You Eat Reveals Who You Are: - Minoru Karasawa; Kazutoshi Sasahara; Hakche Ryu (Maketingu Janaru)
We propose that food choice may serve as a categorical basis for an individual’s self-identity, meaning “what you eat reveals who you are.” This type of social identity, namely, food identity (FI), can be a significant determinant of consumers’ attitudes and behavior. Whereas previous studies on FI have focused mainly on the choice of eating meat, we maintain that concerns about health and the moral implications of eating meat may entail FI involving a broader range of food choices. A food identity scale was constructed to measure the strength of FI among Japanese individuals. A factor analysis revealed two components of FI: health-oriented identity and amusement-oriented identity. The former component of FI was found to connote liberal-leaning values, whereas the latter component was interpreted as a reactionary tendency against the “do-gooder” character of the former. The results, including the value-laden implications, were consistent with evidence from a preceding study analyzing social media data. The roles played by social identity and ethical values with ideological connotations in consumer behavior are discussed.